Thin-layer modeling of convective and microwave-convective drying of oyster mushroom (Pleurotus ostreatus) - Bhattacharya, Mrittika (J Food Sci Technol, 2013)
Oyster mushroom samples were dried under selected convective, microwave-convective drying conditions in a recirculatory hot-air dryer and microwave assisted hot-air dryer (2.45 GHz, 1.5 kW) respectively. Only falling rate period and no constant rate period, was exhibited in both the drying technique. The experimental moisture loss data were fitted to selected semi-theoretical thin-layer drying equations. The mathematical models were compared according to three statistical parameters, i.e. correlation coefficient, reduced chi-square and residual mean sum of squares. Among all the models, Midilli et al. model was found to have the best fit as suggested by 0.99 of square correlation coefficient, 0.000043 of reduced-chi square and 0.0023 of residual sum of square. The highest effective moisture diffusivity varying from 10.16 × 10(−8) to 16.18 × 10(−8) m(2)/s over the temperature range was observed in microwave-convective drying at an air velocity of 1.5 m/s and the activation energy was calculated to be 16.95 kJ/mol. The above findings can aid to select the most suitable operating conditions, so as to design drying equipment accordingly.